A transdiagnostic data-driven study of children's behaviour and the functional connectome. (December 2021) - Jones, Jonathan S.; the CALM Team,; Astle, Duncan E.
Abstract: Behavioural difficulties are seen as hallmarks of many neurodevelopmental conditions. Differences in functional brain organisation have been observed in these conditions, but little is known about how they are related to a child's profile of behavioural difficulties. We investigated whether behavioural difficulties are associated with how the brain is functionally organised in an intentionally heterogeneous and transdiagnostic sample of 957 children aged 5–15. We used consensus community detection to derive data-driven profiles of behavioural difficulties and constructed functional connectomes from a subset of 238 children with resting-state functional Magnetic Resonance Imaging (fMRI) data. We identified three distinct profiles of behaviour that were characterised by principal difficulties with hot executive function, cool executive function, and learning. Global organisation of the functional connectome did not differ between the groups, but multivariate patterns of connectivity at the level of Intrinsic Connectivity Networks (ICNs), nodes, and hubs significantly predicted group membership in held-out data. Fronto-parietal connector hubs were under-connected in all groups relative to a comparison sample and children with hot vs cool executive function difficulties were distinguished by connectivity in ICNs associated with cognitive control, emotion processing, and social cognition. This demonstrates both general and specific neurodevelopmental risk factors in the functional connectome. Highlights: We derived 3 behavioural profiles in 799 neurodevelopmentally at-risk children. Namely, difficulties in hot executive function (EF), cool EF, and learning. Global organisational properties of the functional connectome did not differ. Connector hubs were more globally integrated in controls than at-risk groups. Hot and cool EF groups differed in regional and network connectivity.